2017
DOI: 10.1177/0309364616637955
|View full text |Cite
|
Sign up to set email alerts
|

Stratified cost-utility analysis of C-Leg versus mechanical knees

Abstract: The stratified cost-utility results have relevant clinical implications and provide useful information for practitioners in tailoring interventions. Clinical relevance A cost-utility analysis that considered patients characteristics provided insights on the "affordability" of C-Leg compared to mechanical knees. In particular, results suggest that C-Leg has a significant impact on "mobility" for first-time prosthetic users over 40 years, but implementation of specific low-cost physical/psychosocial intervention… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
42
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 38 publications
(45 citation statements)
references
References 28 publications
3
42
0
Order By: Relevance
“…We identified four studies [16][17][18][19] which reported utilities for C-Leg and NMPK users. Three studies [16][17][18] used the EQ-5D 3L and one study [19] the SF-36/SF-6D. Brodtkorb et al [16] derived utility values directly from the visual analog scale of the EQ-5D which is not the standard method for generating utilities and does not reflect preferences of the society.…”
Section: Utilitiesmentioning
confidence: 99%
See 4 more Smart Citations
“…We identified four studies [16][17][18][19] which reported utilities for C-Leg and NMPK users. Three studies [16][17][18] used the EQ-5D 3L and one study [19] the SF-36/SF-6D. Brodtkorb et al [16] derived utility values directly from the visual analog scale of the EQ-5D which is not the standard method for generating utilities and does not reflect preferences of the society.…”
Section: Utilitiesmentioning
confidence: 99%
“…Compared with non-microprocessor-controlled (mechanical) knee joints (NMPK), the C-Leg reduced the number and frequency of stumbles and falls of up to 80% [6,8,9]. In addition, four studies [16][17][18][19] that analyzed the health-related quality of life (HRQoL) in prosthesis users found improvements in the HRQoL of 14-38% when patients were using the C-Leg instead of NMPKs.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations